2019
DOI: 10.1016/j.gloplacha.2019.102998
|View full text |Cite
|
Sign up to set email alerts
|

Convergent human and climate forcing of late-Holocene flooding in Northwest England

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 100 publications
(151 reference statements)
1
7
0
Order By: Relevance
“…In all cores linear interpolation between the deepest 210 Pb activity and the upper most radiocarbon date in the corresponding piston cores (Table 2) yielded LSR an order of magnitude lower than those generated by the CF:CS model in the upper part of the core. This increase in sedimentation since the 19 th century is consistent with other studies in the area, and could have a number of causes including increases in land erosion due to agriculture and increases in biogenic sediment as a result of increased primary productivity in the lake (Sabater and Haworth, 1995;Schillereff et al, 2019).…”
Section: Age-depth Modelsupporting
confidence: 90%
“…In all cores linear interpolation between the deepest 210 Pb activity and the upper most radiocarbon date in the corresponding piston cores (Table 2) yielded LSR an order of magnitude lower than those generated by the CF:CS model in the upper part of the core. This increase in sedimentation since the 19 th century is consistent with other studies in the area, and could have a number of causes including increases in land erosion due to agriculture and increases in biogenic sediment as a result of increased primary productivity in the lake (Sabater and Haworth, 1995;Schillereff et al, 2019).…”
Section: Age-depth Modelsupporting
confidence: 90%
“…Brown found the biggest impact was made by the NAO (the difference in sea-level pressure between Iceland and the Azores), a positive NAO increases the likelihood of extra-tropical cyclones developing over the North Atlantic. This relationship is further demonstrated by Richardson et al (2017) and Schillereff et al (2019) which both show a negative NAO correlates strongly with increased high-river flows.…”
Section: Introductionmentioning
confidence: 66%
“…Since the empirically determined value of F Pb is 0.47, it appears that the bulk of 210 Pb in the water column of Brotherswater is transported on particulates with a mean size of around 3-4 lm. The particle size analyses carried out by Schillereff et al (2019) revealed the presence of three members (Fig. 7), EM1 (mean particle size 3.21 lm), EM2 (15.65 lm) and EM3 (213.22 lm).…”
Section: Mean Particle Size For Sediments Transporting 210 Pbmentioning
confidence: 98%
“…The bathymetry of the lake (Fig. 1) is dominated by a central flat profundal zone with a maximum depth of 18 m. A recent more accurate survey (Schillereff et al 2019) has determined the lake volume to be 1.33 9 10 6 m 3 , and the mean depth 7.8 m.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation